Potential Geotourism Attractions on Nusa Penida Island, Klungkung Regency, Bali - Ida Bagus Oka Agastya; Putu Diyan Diwyastra; Ketut Ariantana; Yudhistira Satya; Putu Maiva Utama (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2022)
Nusa Penida Island is one of the leading tourist destinations in Bali Province. Tourist destinations on the Island consist of various types of beaches, hills, caves to unique landscapes formed due to the karstification process. Nusa Penida Island is geologically composed of limestones (the Selatan Formation) with various types such as clastic limestones and coral limestones(Hadiwidjojo et al, 1998). In addition to the unique geology of Nusa Penida Island, it also has archaeological uniqueness. The Gede Cave shows that Nusa Penida was once inhabited by prehistoric humans (Abdillah, 2011). During the COVID-19 pandemic, tourism seems to be forced to accelerate and requires new tourist attraction innovations that support sustainable tourism. This research discusses geotourism-based tourist attractions that can be developed and explored in Nusa Penida. The approach used is geological diversity inventory method (Geological Agency, 2017). Primary data was obtained through survey activities. From the research carried out, it can be concluded that 10 geological site locations in the Nusa Penida area have the potential to be developed as areas with geotourism attractions, which offer unique geology, especially regarding karts landscape processes and one of the key geological history on the island of Bali. In addition, Nusa Penida Island has the potential to be developed as a geopark as an effort to develop sustainable tourism in Klungkung Regency.